ASPIC? and the Postulates of Non-interference and Crash-Resistance - Silva, Rafael; Alcântara, João (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2021: Anais da X Brazilian Conference on Intelligent Systems, 2021)
We introduce an interrogation mark ? in ASPIC+ languages as a plausibility operator to enhance any defeasible conclusion does not have the same status as an irrefutable one. The resulting framework, dubbed ASPIC? , is tailored to make a distinction between strong inconsistencies and weak inconsistencies. The aim is to avoid the former and to tolerate the latter. This means the extensions obtained from the ASPIC? framework are free of strong conflicts, but tolerant to weak conflicts. Then, in the current study, we show ASPIC? satisfy reasonable properties. In particular, we focus on the property that a conflict between two arguments should not interfere with the acceptability of other unrelated arguments. With this purpose in mind, we prove under which conditions the important principles of Non-interference and Crash-Resistance hold in ASPIC?.